Effect of Passive Fit Absence in the Prosthesis/Implant/Retaining Screw System: A Two-Dimensional Finite Element Analysis - Gomes, Erica Alves [UNESP]; Assunção, Wirley Goncalves [UNESP]; Tabata, Lucas Fernando; Ricardo Barao, Valentim Adelino [UNESP]; Delben, Juliana Aparecida [UNESP]; Sousa, Edson Antonio Capello [UNESP] (Lippincott Williams & Wilkins, 2009)
The misfit between prostheses and implants is a clinical reality, but the level that can be accepted without causing mechanical or biologic problem is not well defined. This study investigates the effect of different levels of unilateral angular misfit prostheses in the prosthesis/implant/retaining screw system and in the surrounding bone using finite element analysis. Four models of a two-dimensional finite element were constructed: group I (control), prosthesis that fit the implant; groups 2 to 4, prostheses with unilateral angular misfit of 50, 100, and 200 mu m, respectively. A load of 133 N was applied with a 30-degree angulation and off-axis at 2 mm from the long axis of the implant at the opposite direction of misfit on the models. Taking into account the increase of the angular misfit, the stress maps showed a gradual increase of prosthesis stress and uniform stress in the implant and trabecular bone. Concerning the displacement, an inclination of the system due to loading and misfit was observed. The decrease of the unilateral contact between prosthesis and implant leads to the displacement of the entire system, and distribution and magnitude alterations of the stress also occurred.
Keywords: Prosthesis; misfit; biomechanics; dental implants; finite element analysis; stress distribution